Assessing Biodiversity Conservation Strategies and Challenges in India (International Journal of Food and Nutritional Sciences, 2021)
Biodiversity is a critical component of India's natural heritage, supporting ecological balance and providing various ecosystem services. However, the country faces numerous challenges in conserving its diverse and unique biodiversity. The study assesses the effectiveness of existing conservation initiatives, identifies key challenges, and proposes recommendations for enhancing biodiversity conservation efforts. To achieve these objectives, analysis of conservation policies and practices, and examination of case studies were conducted. The findings emphasize the importance of sustainable biodiversity management in maintaining India's ecological integrity, promoting socio-economic development, and fulfilling global environmental commitments. This research aims to critically examine the current state of biodiversity conservation strategies in India and shed light on the associated challenges.